Pengaruh Penambahan Tepung Biji Durian Terhadap Daya Terima Mie Basah Tepung Biji Durian - Nadia Syafira Hestu Wibawani; Riris Oppusunggu; Tiar Lince Bakara; Rumida (Kabar Gizi Indonesia, 2023)
Noodles are very popular with the people of Indonesia because of their taste, texture and practical processing method and the price is relatively cheap so that they are easily accessible to the public. To determine the effect of adding durian seed flour as much as 10%, 20%, 30% in the manufacture of durian seed wet noodles on aspects of color, texture, taste, and flavor, as well as the level of consumer preference for wet noodles. This study was an experimental study using a completely randomized design (CRD) with three trials and two repetitions. The experiment was making wet noodles with the addition of 10%, 20% and 30% durian seed flour. The results showed that the panelists liked the color, texture, taste, and flavor of wet durian seed noodles using the addition of 10% durian seed flour. The addition of different amounts of durian seed flour to the manufacture of durian seed wet noodles had a different effect on the color, texture, and aroma, but did not have a different effect on the taste of the durian seed wet noodles. The panelist's acceptance of the most preferred durian seed wet noodles was the experiment of adding 10% durian seed flour to 90% wheat flour.